Trade, Doha, and Development : A Window into the Issues - Newfarmer, Richard (Washington, DC: World Bank, 2012)
This book traces the development of world trade from the era when the global trading system had been stacked against growth in developing countries to the present time when the membership of the WTO has grown to include most developing countries. It is for this reason that the Doha Round is important: It has given all countries of the world the opportunity to work collectively on barriers of interest to developing countries and to the world's poor. Although the choice is simple, it is not easy. The underlying details of the issues are notoriously complex. Observers have a difficult time penetrating the veil of legal and economic opacity that envelops the negotiations. The details are sufficiently technical and multifarious that experts in one area are often unaware of technical details in another. And details make the difference between opening markets and merely appearing to do so through a vacuous agreement that looks good on the surface but does little or nothing to widen opportunities for poor traders in the global market place. This book provides succinct analyses of the most critical issues facing negotiators, highlighting the choices that most affect development. It is a window into the issues. The WTO negotiations are not the only ones shaping the world trading system. For one thing, regional trade agreements in growing numbers are introducing preferential trade arrangements between subsets of the international community. Then again, a third subject of international policy discussions-"aid for trade"-affects developing countries' opportunities to participate in the global market. This book details the pitfalls for the world economic system to avoid, and the author hopes that it will contribute to a better world trading system, one that is more equitable and more supportive of development.